THE IMAGE OF WAR IN A.GELASIMOV’S NOVEL "STEPPE GODS" - Isaeva Yuliya (Galaxy International Interdisciplinary Research Journal, 2024)
The possibilities of depicting the Great Patriotic War, not based on the writer’s personal experience, as well as the dominant aspects of the image and ethico-social and philosophical emphases are studied. Gelasimov’s A. novel is interpreted not as a new word in war literature, but as an approximation to potential and fruitful artistic trends in modern literature.